Practical applications analysis and economic efficiency of the method on assessment of the sealing action from the tracked mover on the soil layer - E. Peregoodov, N; A. Novak, M (International Journal of Engineering and Technology, 2018)
The article describes and evaluates the economic efficiency of applying a modern approach to solving the problem of soil compaction by tracked movers using a new method based on the theory of hereditary creep of elastoviscoplastic materials, taking into account new factors (the time of the impact of movers on the base, rheological properties of the soil, etc.), as well as using a new devices and techniques for determining the physicoâ€“mechanical characteristics of the soil layer and modern specialized software products.Â Â